W/O high internal phase emulsion featuring by interfacial crystallization of diacylglycerol and different internal compositions - Liu, Yingwei; Lee, Wan Jun; Tan, Chin Ping; Lai, Oi Ming; Wong, Yong; Qiu, Chaoying (Elsevier, 2022)
High internal phase emulsions (HIPEs) show promising application in food and cosmetic industries. In this work, diacylglycerol (DAG) was applied to fabricate water-in-oil (W/O) HIPEs. DAG-based emulsion can hold 60% water and the emulsion rigidity increased with water content, indicating the water droplets acted as “active fillers”. Stable HIPE with 80% water fraction was formed through the combination of 6 wt% DAG with 1 wt% polyglycerol polyricinoleate (PGPR). The addition of 1 w% kappa (κ)-carrageenan and 0.5 M NaCl greatly reduced the droplet size and enhanced emulsion rigidity, and the interfacial tension of the internal phase was reduced. Benefiting from the Pickering crystals-stabilized interface by DAG as revealed by the microscopy and enhanced elastic modulus of emulsions with the gelation agents, the HIPEs demonstrated good retaining ability for anthocyanin and β-carotene. This study provides insights for the development of W/O HIPEs to fabricate low-calories margarines, spread or cosmetic creams.